Design And Development Of Biomechanics Calculation Software For Hand Movement - Wan Ismail Khairudin, Wan Ahmad Firdaus (Universiti Sains Malaysia, 2005)
The analysis of lower limb movements has been well established in biomechanics research and clinical applications for a long time. For these studies, powerful and very advanced tools have been developed to measure movement parameters and reaction forces. The main focus of interest aims towards gait movements while the understanding of the basic concepts is supported by numerous models. Definitions of physiological ranges and detection of pathological changes in movements open an increasingly valuable clinical field of application. If, however, the primary function of the upper extremities as highly variable and adaptive organ for manipulating tasks is the subject of interest, the situation becomes considerably more complex. The nature of free arm movements is completely different from being restricted, repeatable or cyclic as compared to gait. Therefore, the transfer of the knowledge and experience gained in lower extremity movement analysis to the analysis of upper extremities turns out to be difficult. A proposal for how to proceed in measurements, e.g. where to place the markers and how to calculate movements and angles of segments involved, will be discussed which results in the description of the joint movements of wrist, elbow and shoulder joint. The definition of the motion is a specific step in upper extremity motion analysis which is important in terms of repeatability and significance of the results. An example of assessing movement disorders in children with plexus lesion will illustrate the implications and the potential of upper extremity movement analysis in clinical applications.